Intertemporal Cross-Dependence in Securities Daily Returns and the Short-Run Intervaling Effect on Systematic Risk - Hawawini, Gabriel A. (Journal of Financial and Quantitative Analysis, 1980)
Gabriel A. Hawawini, Intertemporal Cross-Dependence in Securities Daily Returns and the Short-Run Intervaling Effect on Systematic Risk, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 1 (Mar., 1980), pp. 139-149